Heterogeneous agent systems - Subrahmanian, V. S. (MIT Press, 2000)
Software agents are the latest advance in the trend toward smaller, modular pieces of code, where each module performs a well-defined, focused task or set of tasks. Programmed to interact with and provide services to other agents, including humans, software agents act autonomously with prescribed backgrounds, beliefs, and operations. Systems of agents can access and manipulate heterogeneously stored data such as that found on the Internet. After a discussion of the theory of software agents, this book presents IMPACT (Interactive Maryland Platform for Agents Collaborating Together), an experimental agent infrastructure that translates formal theories of agency into a functional multiagent system that can extend legacy software code and application-specific or legacy data structures. The book describes three sample applications: a store, a self-correcting auto-pilot, and a supply chain.